EL ÁREA DE SUPERFICIE CORPORAL: UN FACTOR PREDICTOR DE CONVERSIÓN EN CIRUGÍA COLORRECTAL LAPAROSCÓPICA (Revista Argentina de Cirugía, 2022)
Background: Body surface area is a measurement used in cIinicaI settings. Its impact on Iaparoscopic coIorectaI surgery has not been previousIy studied.Objective:To assess the impact of body surface area on conversion rate.Design: Retrospective anaIysis of prospectiveIy coIIected data.Setting: SingIe tertiary care institution.Patients: 916 consecutive patients operated on between January 2004 and August 2011 were identified from a prospectiveIy database.Main outcome measures: Conversion rate was anaIyzed reIated to age, gender, obesity, disease Iocation (coIon vs. rectum), type of disease (neopIastic vs. non-neopIastic), history of previous surgery, and body surface area; body sur- face area was caIcuIated by MosteIIer formuIa. Body surface area was anaIyzed using median and quartiIes cut off vaI- ues (1.6, 1.8 and 2.0). Logistic regression was used to anaIyze the association between body surface area and conver- sion, adjusting for different confounders. Interaction between body surface area and body mass index was checked and not found.Results: OveraII conversion rate was 10%. Median body surface area was 1.84 (range: 1.14-2.53).Conversion rates for quartiIes 1, 2, 3 and 4 were: 4.4%, 8.3%, 12.7%, and 14.8%, respectiveIy, p = 0.001. Patients with body surface area> 1.8 (N=503) had a higher conversion rate than those with body surface area < 1.8 (N=413) [13.8% vs 6.3%, respec- tiveIy, OR: 2.35 (95% CI: 1.45-3.86; p=0.0001)]. MuItivariate anaIysis showed that body surface area > 1.8 was associ- ated with conversion (OR: 2, 95% CI: 1.1-3.7, p=0.023) after adjusting for gender, age, and previous surgery...
Keywords: laparoscopic colorectal surgery; body mass index; results